Sensing and Imaging based on novel laser techniques - Myo, Myat Thu (2017)
The purpose of this project to understand the development of the sensing and imaging system based on the optic and photonics. Base on the technology use on the real prototype, the applications may vary. The development of the terahertz lasers with mid infrared quantum cascade laser, the photons emitted with electrons intersubband transition within the conduction band. So, the wavelength, barrier width, and the quantum-well structures and the intensity noise are main challenge because of the population inversion between the two energy levels. I have experiment on the quantum cascade lasers (QCL) relate to intensity noise ratio (RIN) in the operation of continuous wave (cw). I observe on the properties of intensity noise for the intensity noise ratio. By increasing the output power of quantum cascade lasers can obtain different intensity noise ratio in interband semiconductor lasers. In semi classical model, the result show impact on active regions of the three laser levels. This paper show the calculation of RIN in QCLs, gain stage effect of noise frequency.